2016
DOI: 10.3390/rel7050053
|View full text |Cite
|
Sign up to set email alerts
|

History, Culture and Traditions: The Silent Spaces in the Study of Spirituality at the End of Life

Abstract: Recent increase in the number of studies on spirituality manifests growing recognition of the importance of spirituality, as well as mounting interest in studying spirituality in healthcare. Most studies on spirituality in end of life care focus on identifying specific features of spirituality and often represent an individualistic understanding of spirituality. They seldom engage in a historical-cultural exploration of the contextual meanings of those features of spirituality. This paper aims to demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
5
0
1
Order By: Relevance
“…Dvasingumas yra vienas iš žmogaus gyvenimo kokybės rodiklių (Lee, 2018). Sveikatos priežiūros kontekste dvasingumas dažniausiai vertinamas kaip visapusiškos ir į asmenį orientuotos priežiūros sąlyga (Inbadas, 2016). Per pirmuosius tris nepriklausomybės dešimtmečius Lietuvoje buvo atlikta dešimtys teorinio ir praktinio pobūdžio tyrimų, susijusių su dvasingumu, dvasine kultūra bei egzistencine gerove, ir tokių tyrimų skaičius tolygiai auga (Palijanskaitė, 2009).…”
Section: įVadasunclassified
“…Dvasingumas yra vienas iš žmogaus gyvenimo kokybės rodiklių (Lee, 2018). Sveikatos priežiūros kontekste dvasingumas dažniausiai vertinamas kaip visapusiškos ir į asmenį orientuotos priežiūros sąlyga (Inbadas, 2016). Per pirmuosius tris nepriklausomybės dešimtmečius Lietuvoje buvo atlikta dešimtys teorinio ir praktinio pobūdžio tyrimų, susijusių su dvasingumu, dvasine kultūra bei egzistencine gerove, ir tokių tyrimų skaičius tolygiai auga (Palijanskaitė, 2009).…”
Section: įVadasunclassified
“…It has recently been suggested that current discussions of spirituality, especially in the realm of healthcare, lack a sense of its historical and cultural backgrounds (Inbadas 2016). Standard narratives purporting to tell the history of spirituality go in one of two directions: some are focused exclusively on the modern usage of 'spirituality' and narrate the recent career of the term as produced by the ongoing transformation of institutional forms of religion.…”
Section: Introductionmentioning
confidence: 99%
“…Inbadas [25] further highlights the cultural dimension of spirituality in palliative care. He calls for the need to find practical expressions of spirituality, and underlines the importance of attending to the "cultural embeddedness" of spirituality at such times ( [25], p. 7). He recognises, in keeping with our proposed definition, that meaning, purpose and transcendence are key aspects of personal spirituality.…”
Section: Spiritual Care From Childhood To the End Of Lifementioning
confidence: 99%